Morpho-cultural and pathogenic variability in Rhizoctonia solani isolates from rice, maize and green gram - S.N. RAI, AVINASH SINGODE; C. MANJUNATHA, P.K. MISHRA, ROBIN GOGOI*, P.K. SINGH (Indian Phytopathology, 2014)
Twenty two isolates of Rhizoctonia solani collected from rice (10), maize (10) and green gram (2) were studied for their variability with respect to cultural, morphological characters and pathogenicity. Colony appearances of the isolates were sparse, sparse fluffy, cottony and cottony fluffy. Most of the isolates were sparse and light brown in colour. Out of the three patterns of radial growth namely fast, medium and slow, twelve isolates were medium growing where growth completed within 72h, eight isolates were fast growing (48h) and two isolates were slow growing (96h or more). Sclerotia of the isolates were light brown, brown, dark brown and black in colour and formed as central, sub-central ring, peripheral ring, scattered and irregular manner. Majority of the isolates produced high number of sclerotia ranging from 40 to 60 within 3 to 10 days. Cross infectivity of the isolates was positive in all the three hosts with variability in their pathogenicity. Four isolates of rice, two each of maize and green gram isolates were found more aggressive and produced higher incidence of disease which could be utilized in resistant breeding programmes of their respective hosts. Cluster analysis showed four separate groups for the rice and maize isolates of R. solani, however the green gram isolates clustered with maize isolates.